NUTRITION AS A RISK FACTOR FOR CARDIOVASCULAR DISEASES (FROM THE RESULTS OF THE PURE STUDY IN SIBERIA) - Tsygankova, Daria Pavlovna; Swarovskaya, Polina Konstantinovna; Bazdyrev, Evgeny Dmitrievich; Artamonova, Galina Vladimirovna; Barbarash, Olga Leonidovna (Bajkalʹskij medicinskij žurnal, 2023)
Introduction. Over the past 50 years, epidemiological studies have actively studied the effect of nutrition on the cardiovascular system. Large-scale studies have confirmed the role of nutrition in terms of global reduction in the risk of cardiovascular disease. It has been established that a rational diet reduces the risk of developing cardiovascular pathology by influencing cardiovascular risk factors. Purpose: to assess the qualitative composition of dietary stereotypes of Siberian residents and its role in the development of the main factors of cardiovascular risk. Material and methods. To analyze the daily diet, respondents were examined in the framework of the international study PURE, aged 35-70 years (n=353). A questionnaire was used for a semi-quantitative assessment of the frequency of food consumption by the adult population with further use of the own computer program “Assessment of the relationship between nutritional characteristics and its nutritional value and the prevalence of cardiovascular diseases and their risk factors among the urban and rural population” (RU 2019662710). Factor analysis identified three stereotypes of eating behavior: the first included the consumption of thermally processed and unprocessed vegetables, in season and throughout the year, as well as fruits throughout the year; the second - the consumption of non-dietary meat, complex carbohydrates and sweets, the third included persons who were not defined by the previous two stereotypes. Results. The first stereotype was associated with an increased risk of developing hypertriglyceridemia (OR=1.44, at 95% CI: 1.0-2.0, p=0.029) and obesity (OR=1.9, at 95% CI: 1.4- 2.5, p<0.001). Adherence to the second - with a reduced risk of developing a low level of HDL (OR = 0.58, at 95% CI: 0.4-0.8, p = 0.001), a high level of LDL (OR = 0.58, at 95% CI : 0.38-0.9, p=0.015), hypertriglyceridemia (OR=0.54, 95% CI: 0.4-0.7, p<0.001), hypercholesterolemia (OR=0.63, 95% CI : 0.44-0.9, p=0.013), obesity (OR=0.61, 95% CI: 0.4-0.8, p=0.002). In a qualitative analysis of the components of the selected stereotypes, it was determined that an excess amount of protein (more than 0.6-0.83 g/kg of body weight) was consumed by 55.5% of persons who followed the second nutritional stereotype, 42.7% - the third and 39.8 % - the first (p=0.052). Excess fat (more than 70-15 g/day for men and 60-102 g/day for women) was consumed by 100% of persons with the first and second stereotypes and 97.7% with the third (p=0.163). An excessive amount of carbohydrates (more than 257-586 g/day) was noted in 1.0% of respondents with the second stereotype and 1.5% with the third. Persons with the first nutritional stereotype did not show excessive consumption of carbohydrates (p=0.674). When conducting a logistic regression analysis, it was found that excess protein in the diet of Siberian residents was associated with a decrease in the risk of developing arterial hypertension (OR=0.6, CI:0.3-1.1, p=0.113) and high levels of low-density lipoproteins (OR=0.5, CI:0.3-0.98, p=0.447), but not statistically significant, as well as diabetes mellitus (OR=0.59, CI:0.3-0.99, p=0.044 ) and obesity (OR=0.4, CI:0.2-0.6, p<0.001). Conclusions. Despite generally accepted international recommendations, the first dietary stereotype was associated with the development of hypertriglyceridemia and obesity, in contrast to the second stereotype (which was associated with a reduced risk of dyslipidemia and obesity). In addition, excess protein intake was associated with a reduced risk of diabetes and obesity, which is contrary to WHO recommendations for healthy eating. Taking into account the results obtained, it is necessary to continue studying the nutritional habits of the inhabitants of Siberia in order to modernize the principles of healthy nutrition.